A Comprehensive Learning Experience Through Dance: The Case of Isla Venado 2005-2015 - Marenco Rojas, Helen (2023)
The approach to this case allows us to place dance as a mediating factor in the learning shared with students from the National University during the university extension experience on Isla Venado carried out within the framework of the Comprehensive Development Program for Rural Rural Communities of the Gulf. from Nicoya. The involvement found in the concept of movement is exposed as the main axis of the system. Thus, two meanings of order are subtracted from its epistemic root; on the one hand, external movement and on the other, internal movement. Both actions come together behind the scenes in a dance that invites us to move towards a unique stage between sky, sun, sea and salt. This document exposes the elements necessary to demonstrate a university extension process, its achievements, interdisciplinary work and local impact.